2012
DOI: 10.1007/s11356-012-0775-6
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of Orange G dye under solar light using nanocrystalline semiconductor metal oxide

Abstract: The adsorption of dye onto catalytic surface was analysed employing model equations such as Langmuir and Freundlich isotherms, and it was found that the Langmuir isotherm model best fitted the adsorption data. The solar photodegradation of OG followed pseudo-first-order kinetics. HPLC and ESI-Mass analyses of the degraded samples suggested that the dye molecules were readily degraded under solar irradiation with nanocrystalline ZnO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…These intermediate products arise from the random attack of hydroxyl free radicals at several sites on the orange G dye molecule [44]. Table 2 shows a comparative study between the fabricated MgO photocatalyst in our study and other photocatalysts in the literature such as ZnO, Mn-doped-ZnO, carbon nitride/ AgBr, and CaBiVMoO 8 [44][45][46][47]. The comparison confirmed that the fabricated MgO efficiently degrades the orange G dye.…”
Section: Photocatalytic Degradation Of Orange G Dyesupporting
confidence: 57%
See 2 more Smart Citations
“…These intermediate products arise from the random attack of hydroxyl free radicals at several sites on the orange G dye molecule [44]. Table 2 shows a comparative study between the fabricated MgO photocatalyst in our study and other photocatalysts in the literature such as ZnO, Mn-doped-ZnO, carbon nitride/ AgBr, and CaBiVMoO 8 [44][45][46][47]. The comparison confirmed that the fabricated MgO efficiently degrades the orange G dye.…”
Section: Photocatalytic Degradation Of Orange G Dyesupporting
confidence: 57%
“…After that, OH . directly oxidize orange G dye to intermediates and mineral salts then finally to CO 2 and H 2 O which considered non-toxic and ecofriendly products [31,[36][37][38][39][40][41][42][43][44][45][46][47]. The major intermediates were (3) ln H o ∕H t = K t Fig.…”
Section: Photocatalytic Degradation Of Orange G Dyementioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Broad band gap issues can also be overcome by introducing a hetero or homo barrier made with a combination of different metal oxides, 8 nanowire, 9 core-shells 9 and nanowires, 10 which offers superior charge transfer competence and commotion compared to a sole metal oxide semiconductor. [11][12][13] This allows the competent and viable catalysts to perform under visible light irradiation, which constitutes nearly 46% of the astral band. 14 In recent years, the investigation of semiconductors for harvesting energy in the visible spectrum has led to the progression of the invention of non-titania-based semiconducting photocatalysts for dye degradation.…”
Section: Introductionmentioning
confidence: 99%
“…At this time, several methods such as capillary electrophoresis [5], electrochemical methods [6,7], separation methods [8,9], photometric method [10,11] and spectrophotometric method [2,12,13] are reported for the determination of dyes. However some of these methods are not suitable for routine monitoring as they are time consuming, complicated, and have poor sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%